The EU scheme for the state aid rules in the air transport sector during the Covid-19 crisis - Dubravka Aksamovic; Lidija Simunovic (Juridical Tribune, 2022)
Paper provides for a systematic overview of the EU scheme for the State aid rules applicable to the air transport sector during Covid-19 crisis. The COVID-19 outbreak is having a major impact on European air transport sector. In order to help air transport undertakings in Europe to overcome the financial troubles, to preserve jobs, to secure supply of essential food, medicals or other items, etc., the EU Commission adopted set of legislative measures enabling the EU Commission and Member States to authorise hundreds of State aid measures, not only to air transport sector, but also to other economic sectors, which were mostly affected by the pandemic. Since in normal circumstances member states State aid to national undertakings are subject to extremely stringent EU competition law regime, the intention of this paper is, firstly, to analyse to what extent and under what conditions that has changed during pandemic. Secondly, the intention of the paper is to explore to what extent and for what purposes different Member States granted State aid to their airline industries with special respect to the French, Austrian, Swedish and Croatian State aid policy. Lastly, the authors will raise question whether massive capital injection to air transport companies being made only by certain, wealthier, member states are going, in long term, to cause negative impacts on the competition in the air transport sector in the internal market.